Pemberdayaan Ibu Muda Melalui Program Sekolah Orang Tua Hebat di SPS Catleya 71 Kecamatan Sumbersari Kabupaten Jember - Amanda Dwi Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Indonesian family is currently faced with challenges such as a lack of a mother's knowledge of child rearing, which can have an impact on child growth. It is crucial and markers that the need to improve competence as parents, so therefore the Great Parent School provides a way to address the issues of parenting practices. The study aims to describe the empowerment of young mothers who have attended a Great Parents' School. The study uses a qualitative approach with a descriptive method, the informans in the study are young mothers who have gone through the Great Parents School program and accompanying facilitators, while the data collection process uses observation, interview and documentation with the research location at SPS catleya 71, Sumbersari District, Jember Regency. The results of these studies show the process of empowerment refers to the assumed theories of ACTORS that means authority, confidence, trust, opportunity, responsibility, and support for mothers who have attended Great Parents Schools. Mothers who have attended the Great Parents School have experienced improvements in their knowledge, attitudes and skills regarding parenting experiencing improvements in terms of knowledge, attitudes and skills regarding child care which can be reviewed through an understanding of the role of parents, the implementation of family functions such as instilling religious values, love, and as a protective function as well as the implementation of parenting patterns and the implementation of discipline and understanding communication skills. So it can be concluded that a great school of parents provides a bridge for mothers to be more empowered by the improvements in parenting.
Entry oleh Arif 2026 Januari 27
Keywords: Empowerment; Great Parenting School Program; Parenting